Das Archiv des Körpers: Konstruktionsapparate, Materialitäten und Phantasmen - Bublitz, Hannelore (transcript, 2018)
The human body is more than physical materiality. As the central »organ« of society, it refers to something it has never been: nature and naturalness. Instead, bodies have always been techno bodies: naturally artificial. Besides the metaphors of machines, the phantasm of controllability and the engineering practicability, the body is subject to a visual attractor of a libidinous economy. Its fascination is that which it is not or cannot be as a physical body beyond technical body modifications: a (self-perfecting) machine. This volume by Hannelore Bublitz reconstructs how discourses, technology/-ies and phantasms materialize in the body.